Deliberating across Difference: Religious Accommodation and Deliberative Democracy - Afsahi, Afsoun (Journal of law, religion and state, 2020)
This paper examines two cases of deliberation on the issue of religious arbitration in Canada: first, the Sharia law debate in Ontario (deliberation in the larger public sphere); and second, a deliberation on religious arbitration in British Columbia (deliberation in a small-scale structured setting). Relying on both secondary and original data, this article demonstrates that while the Sharia law debate failed to fulfill the key functions of a deliberative engagement, the small-scale deliberation was able to achieve all three functions: participants had the chance to express their opinions; there was ample dialogue and communication evident by increased empathy, perspective-taking ability, and knowledge gains; and finally, participants were able to come to a decision, however broad, together. Through this comparison, the article highlights key barriers to deliberation across differences and concludes with some suggestions for carrying out such engagements in the future.